Hydrology and conservation of intermountain wetlands - Sanderson, John, author; Steingraeber, David A., advisor; Sanford, William, committee member; Poff, N. LeRoy, committee member; Cooper, David J., committee member (Colorado State University. Libraries, 2006)
To protect biodiversity in the arid intermountain valleys of the western U.S., hydrology and biology must be integrated in wetland management. This dissertation takes a step in that direction for Colorado's San Luis Valley. The dissertation has three major components: (1) an investigation of evapotranspiration (ET) from five intermountain wetlands, (2) an assessment of current and simulated hydrologic conditions in an intermountain playa wetland complex, and (3) research on factors, including flooding, that govern the distribution of plant species in this playa complex. In intermountain valleys, ET is the primary means of water loss. In order to improve its estimation, ET was measured in five herbaceous wetlands using the Bowen ratio energy balance method. Annual ET and the ground water component of ET (ETg) were calculated, and the relationship of ETg to water table depth was determined and compared to existing models. The calculated decrease in annual ETg with water table decline to 1.0 m was as little as 30% of previous predictions. This study also demonstrated that the relationship of ETg to water table depth differs markedly between ground water and surface water wetlands. A resulting model of ET was applied at an intermountain playa, where current hydrologic function was compared to the historical (natural) flow regime. No quantitative approach had been previously been used to assess how hydrologic alteration has affected these ecosystems. The simulated unaltered (i.e., natural) hydrologic regime differed substantially from current conditions with respect to depth, variability, and frequency of flooding, on both an intra-annual and inter-annual basis. The altered hydrologic regime of intermountain wetland ecosystems appears to have significant biological effects. For example, hydrologic alterations were implicated in a decrease in density of the rare plant Cleome multicaulis from 55.6 to 0 stems/m2 over five years. Also, this study provided inferential evidence that abiotic factors, including inundation as affected by hydrologic alteration, are a major determinant of vegetation zone distribution across the entire elevation gradient of this playa. Given the importance of abiotic factors, restoration of a natural flow regime can be expected to contribute significantly to restoring ecological function.
Keywords: ecology; hydrology; hydrologic sciences